Structural-Semantic and Stylistic Characteristics of the New Idioms in Russian Language: Структурно-семантическая и стилистическая характеристика новых фразеологизмов русского языка (Journal of the College of Languages (JCL), 2020)
This study is dedicated to one of the most difficult topics in Russian - this is the science of idioms. A feature of the Russian speech application in recent decades has been the effective change in the lexical composition of the Russian language. This article illustrates the semantic, grammatical and stylistic structural characteristics of the linguistic units that appeared in Russian at the end of the 20th century - the beginning of the twenty-first century. This work defines these terms : terminology, linguistic unity, and terms that are used as synonyms. In this research , we will adhere to the conciliatory view of the problem and include not only the terminology in the language units, but also the terminological compositions, sayings, and composite terms that have been subject to pictorial rethinking. The scientific principles of the various authors are described and analysed, as well as an analysis of many literary examples.Данная статья посвящена одной из наиболее сложных тем русского языка – это фразиология. Особенностью российской речевой практики последних десятилетий является активное изменение лексического состава русского языка. В статье описывается семантическая, структурно-грамматическая и стилистическая характеристика фразеологизмов, появившихся в русском языке в конце XX – начале XXI вв. В работе дается определение данным терминам – фразеологизм, фразеологическая единица, фразеологический оборот, использующиеся в качестве синонимов. В данной статье мы Будем придерживаться синкретического взгляда на проблему и включать в число фразеологизмов не только идиомы, но и фразеологические сочетания, крылатые слова и терминологические сочетания, которые подверглись образному переосмыслению. Характерзируются и анализируются научные положения разных авторов. а также проводится анализ многих литературных примеров.